MOTIVATING HUMAN RESOURCES IN DEVELOPING CORPORATION’S COMPETITIVENESS (Fokus Ekonomi, 2009)
The process of the employee’s motivation emerges from the unfulfilled needs. It needs to find out various ways to motivate the underlying so that they can be productive to achieve their needs. The behavior is evaluated by the employer in order to get a reward or punishment. Then the employees will re-evaluate the unfulfilled needs. The manager can encourage the employee’s motivation through some policies, such as fulfilling the employee’s needs, involving in decision making process, redesigning all jobs, enriching jobs, delegating authority, giving incentives, creating  job environment, having positive enforcement, having specific goals and clear system operational procedure. If the employee’s motivation is high, it will increase high job productivity which can yield in competitiveness.